2017
DOI: 10.1113/jp273684
|View full text |Cite
|
Sign up to set email alerts
|

A Western‐style obesogenic diet alters maternal metabolic physiology with consequences for fetal nutrient acquisition in mice

Abstract: Key points In the Western world, obesogenic diets containing high fat and high sugar (HFHS) are commonly consumed during pregnancy, although their effects on the metabolism of the mother, in relation to feto‐placental glucose utilization and growth, are unknown.In the present study, the consumption of an obesogenic HFHS diet compromised maternal glucose tolerance and insulin sensitivity in late pregnancy in association with dysregulated lipid and glucose handling by the dam.These maternal metabolic changes ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 59 publications
(125 reference statements)
9
70
0
Order By: Relevance
“…; Howell & Powell, ; Musial et al . ; Ye et al . ); however, our study is the first to focus on the effect of consuming high levels of LA with matched total fat and n‐3 content on offspring outcomes, and maternal circulating factors that may affect fertility and development.…”
Section: Discussionmentioning
confidence: 97%
“…; Howell & Powell, ; Musial et al . ; Ye et al . ); however, our study is the first to focus on the effect of consuming high levels of LA with matched total fat and n‐3 content on offspring outcomes, and maternal circulating factors that may affect fertility and development.…”
Section: Discussionmentioning
confidence: 97%
“…The pipeline we developed was applied to investigate the lipid profile of two groups of mice (one lean and one obese) that represent a model of obesity with gestational diabetes [18][19][20]. Mouse brain, liver, heart, kidney, vastus lateralis muscle, and adipose tissue were run in the same sample batch with serum from the same individual animals.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that HFD or overnutrition during pregnancy increased the expression of the genes involved in ECM interactions and metabolic pathways, might promote placental development, and ultimately lead to an overgrowth of the foetus. Many studies using an obesogenic diet before or during gestation have demonstrated that a high-sugar diet or HFD increases the expression of glucose and amino acid transporters in the placenta and ultimately induces foetal growth [27] [28][29][30]. However, our results did not reveal any glucose or amino acid transporter proteins to be differentially expressed but indicated increased expression of genes involved in ECM interactions and metabolic pathways, may indicate nutrients from the maternal diet might not directly influence the RNA levels of nutrient transporter genes in the placenta but promote placental development and ultimately lead to foetal growth.…”
Section: Discussionmentioning
confidence: 99%